Preventing Aggregation of Recombinant Interferon beta-1b in Solution by Additives: Approach to an Albumin-Free Formulation - Najmeh Mahjoubi; Mohammad Reza Fazeli; Rassoul Dinarvand; Mohammad Reza Khoshayand; Ahmad Fazeli; Mohammad Taghavian; Hossein Rastegar (Tabriz University of Medical Sciences, 2015)
Purpose: Aggregation suppressing additives have been used to stabilize proteins during manufacturing and storage. Interferonβ-1b is prone to aggregation because of being non-glycosylated. Aggregation behavior of albumin-free formulations of recombinant IFNβ-1b was explored using additives such as n-dodecyl-β-D-maltoside, Tween 20, arginine, glycine, trehalose and sucrose at different pH. Methods: Fractional factorial design was applied to select major factors affecting aggregation in solutions. Box-Behnken technique was used to optimize the best concentration of additives and protein. Results: Quadratic model was the best fitted model for particle size, OD350 and OD280/OD260. The optimal conditions of 0.2% n-Dodecyl-β-D-maltoside, 70 mM arginine, 189 mM trehalose and protein concentration of 0.50 mg/ml at pH 4 were achieved. A potency value of 91% ± 5% was obtained for the optimized formulation. Conclusion: This study shows that the combination of n-Dodecyl-β-D-maltoside, arginine and trehalose would demonstrate a significant stabilizing and anti-aggregating effect on the liquid formulation of interferonβ-1b. It can not only reduce the manufacturing costs but will also ease patient compliance.